Pengaruh Jiwa Kewirausahaan Dan Nilai Kewirausahaan Terhadap Kemandirian Usaha (Studi Kasus Pada Pengusaha Kuliner Di Pasar Deli Tua) - Sania Tri Nurhayati; Dahrul Siregar; Syafrida Hafni Sahir; Isnaniah Isnaniah (Universitas Medan Area, 2023)
The purpose of this study was to determine and analyze the effect of work facilities and incentives on the independence of culinary entrepreneurs in the Deli Tua Market. The research method used is exploratory research, where the variables are measured using a Likert scale. Methods of data collection is done by interview (interview), with a list of questions (questionnaire) and study documentation. The population in this study were all members of the Culinary Entrepreneurs at Deli Tua Market, totaling 39 people. Sampling with the saturated sampling method or better known as the census. In this study, the population was relatively small, as many as 39 people. Data processing using SPSS version 23 software, with descriptive analysis and multiple regression analysis hypothesis testing. The results of the study show that:(1) partially the entrepreneurial spirit variable affects the business independence of members in Culinary Entrepreneurs at Deli Tua Market. ; (2) partially the entrepreneurship value variable affects the business independence of members in Culinary Entrepreneurs at Deli Tua Market;(3) Simultaneously there is a positive and significant influence between the entrepreneurial spirit variable and the entrepreneurial value of the member's business independence in Culinary Entrepreneurs at Deli Tua Market